Architecture, Memory, and the Idea of Nature - Norman Crowe (Oz, 1990)
Past and Present The practice of keeping old things primarily because of their association with the distant past has always been with us. In past societies it was the temple relic and the talisman. Today their equivalents are found in museum collections and archives...